Analisis Keamanan Website Menggunakan Teknik Footprinting dan Vulnerability Scanning - erick irawadi alwi; Herdianti Herdianti; Fitriyani Umar (Faculty of Computer Science, University of Jember, 2020)
Website security is an effort to protect websites from hacker attacks connected through a network. Website security needs to be a concern in the midst of many cases of website hacking from irresponsible people, including websites at Indonesian tertiary institutions that provide information and services to the public, students, and alumni of tertiary institutions. Higher education institution websites that can be accessed widely online can create vulnerabilities against threats from hacker attacks. To minimize this vulnerability, it is necessary to test the website of the higher education institution to assess and evaluate the security system of the university's website. The research method used in this study is the Ethical Hacking method which focuses on footprinting techniques and vulnerability scanning by only testing passive attacks. The results of this study have found information related to the target website (the website of an educational institution in one of the cities in Indonesia) and several vulnerability alerts after testing vulnerability scanning with high to low risk levels so that researchers recommend improving vulnerability to minimize security holes exploited by hackers .